Duloxetine treatment adherence across mental health and chronic pain conditions - Able SL; Cui Z; Shen W (Dove Medical Press, 2014)
Stephen L Able,1 Zhanglin Cui,2, Wei Shen2 1Global Health Outcomes, Eli Lilly and Company, Indianapolis, IN, USA; 2Global Statistical Sciences, Eli Lilly and Company, Indianapolis, IN, USA Purpose: This study applied a uniform methodology for measuring and comparing duloxetine adherence in the treatment of multiple chronic medical conditions. Materials and methods: Study patients 18–64 years of age initiating duloxetine therapy during 2008 were identified from a large managed care database. The study was restricted to patients with continuous health plan eligibility for 12 months pre- and post-duloxetine initiation. Study patients had ≥1 medical claim with an inpatient or outpatient diagnosis of one (and only one) of the following conditions: major depressive disorder (MDD); generalized anxiety disorder (GAD); fibromyalgia, diabetic peripheral neuropathic pain; or chronic musculoskeletal pain, as established in studies in patients with osteoarthritis and chronic lower back pain (CLBP). Patients initiating duloxetine who had two or more of the six studied conditions were not included in this study, thereby avoiding the need to differentiate between primary and secondary diagnoses from the claims records. Adherence rate was defined as the percentage of patients with a 365-day medication possession ratio ≥0.8. Results: A total of 20,490 patients initiated duloxetine treatment during 2008 with a diagnosis of one of the studied conditions during the study period. The adherence rate in our sample was 34.6% and was highest among patients with MDD (37.3%) and lowest for patients with CLBP (29.9%). In general, adherence among patients with MDD and GAD was greater than among those with a chronic pain condition. Conclusion: Adherence among newly initiated duloxetine patients varied modestly across the medical conditions for which it was used. After adjusting for potential confounders, differences between the mental conditions (MDD and GAD) and the chronic pain conditions (CLBP, osteoarthritis, and diabetic peripheral neuropathic pain) were statistically significant. These results may be useful in the determination of expectations of adherence, and how it may differ for each of the conditions studied. Keywords: adherence, duloxetine, major depressive disorder, generalized anxiety disorder, chronic lower back pain, diabetic peripheral neuropathic pain